Dynamic fracture of C/SiC composites under high strain-rate loading: microstructures and mechanisms. (September 2015) - Li, T.; Fan, D.; Lu, L.; Huang, J.Y.; E, J.C.; Zhao, F.; Qi, M.L.; Sun, T.; Fezzaa, K.; Xiao, X.H.; Zhou, X.M.; Suo, T.; et al.
Abstract: We investigate dynamic fracture of C/SiC composites under high strain-rate compression or tension with split Hopkinson pressure bar (SHPB) and gas gun loading. Components of the as-fabricated composites are mapped and quantified with X-ray computed tomography, including C fibers and fiber bundles, SiC matrix, and inter- and intrabundle voids. Compression loading is applied along the out-of- and in-plane directions by SHPB at strain rates of 10 2 –10 3  s −1 along with in situ X-ray phase contrast imaging. Out-of-plane direction compression and tension are examined with gas gun impact at strain rates 10 4 –10 5  s −1 . For the out-of-plane loading, compression induces fracture via void collapse and shear damage banding, while delamination dominates fracture for the in-plane direction compression. With increasing strain rates, the compression failure modes transit from interbundle to intrabundle fracture of SiC, and then to fiber and bundle breaking. Tensile failure involves delamination, fiber pullout and fiber breaking. In contrary to normal solids, dynamic tensile or spall strength decreases with increasing impact velocities, owing to compression-induced predamage before subsequent tensile loading.